Study of Making Carrot Crackers (Daucus carota) with Addition of Milkfish (Chanos chanos) - Sri Minrti Iskandar; Muhammad Rais; Ratnawaty Fadilah (Jurnal Pendidikan Teknologi Pertanian, 2021)
AbstractHis study aims to determine the nutritional quality of carrot crackers (Daucus carota) with the addition of milkfish (Chanos chanos) as well as panelists' acceptance of carrot crackers. The study used a non-factorial complete randomized design with three and three replications. The treatment in this study was P1 = 50% carrot pulp + 50% milkfish, P2 = 60% carrot pulp + 40% milkfish, P3 = 70% carrot pulp + 30% milkfish. Observation data were analyzed using Variety Analysis (ANOVA) then followed by Ducan Test. The results showed that fish concentration and carrot concentration had an effect on water content, protein content, vitamin A, color, aroma, taste, texture. The best treatment of carrot crackers with the addition of fish is by treatment, P1 = 50% carrot pulp + 50% milkfish, in terms of water content, protein, vitamin A, color, aroma, taste, and texture.Keywords: Crackers, Milkfish, Carrots